2009
DOI: 10.1080/08964280903232035
|View full text |Cite
|
Sign up to set email alerts
|

Key Factors in Smoking Cessation Intervention Among 15–16-Year-Olds

Abstract: The authors aimed to investigate factors associated with smoking cessation among adolescents after tobacco intervention. They examined smokers (n = 127) from one birth cohort (n = 545) in the city of Kotka in Finland. These smokers were randomized in 3 intervention groups the dentist (n = 44) and the school nurse (n = 42 groups), and a control group (n = 39). After 2 months, the authors sent a follow-up questionnaire to the initial smokers to find out who had quit.The authors found that those whose best friend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
13
3

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 41 publications
3
13
3
Order By: Relevance
“…Nicotine administration has been shown to ameliorate these negative affective states [62, 63]; thus, it could be argued that affect and mood regulation is promoted by continued tobacco use in late chronotypes. Relatedly, increases in affective states such as anger [64] and impulsivity [65] following smoking cessation predict relapse while cessation has been reported by early chronotypes as “easier” [66]. Promoting adequate sleep and earlier sleep preference and timing may be a viable smoking cessation intervention component.…”
Section: Discussionmentioning
confidence: 99%
“…Nicotine administration has been shown to ameliorate these negative affective states [62, 63]; thus, it could be argued that affect and mood regulation is promoted by continued tobacco use in late chronotypes. Relatedly, increases in affective states such as anger [64] and impulsivity [65] following smoking cessation predict relapse while cessation has been reported by early chronotypes as “easier” [66]. Promoting adequate sleep and earlier sleep preference and timing may be a viable smoking cessation intervention component.…”
Section: Discussionmentioning
confidence: 99%
“…Adolescent boys were found to be more morningnessoriented than girls in a study by Heikkinen, Broms, Pitkäniemi, Koskenvuo, and Meurman (2009), while Japanese office workers aged between 20 and 50 who were studied by Ishihara, Miyake, Miyasita, and Miyata (1992), were found to have an intermediate disposition, and Díaz-Morales and Sanchez-Lopez (2004) recorded that people over the age of 50 in their study tended toward morningness.…”
mentioning
confidence: 93%
“…Earlier studies, mostly with relatively small sample sizes, have demonstrated an association between diurnal type and smoking, such as among university students in Japan [3], 14 to 94 year olds in Germany and Austria [4], Hungarian adolescents [5], as well as Finnish adolescents [6] and adults [7]. These are in line with our recent study of Finnish twins [7] indicating that by using a single question on diurnal type, the Fagerström Test for Nicotine Dependence (FTND) [8] and DSM-IV (Diagnostic and Statistical Manual of Mental Disorders) diagnosis of nicotine dependence (ND) [9] the evening type was strongly associated with not only being a smoker but also with ND.…”
Section: Introductionmentioning
confidence: 99%